Implementation of the Adoption of Technology Innovation Processes of Calina Papaya in Farmer Women's Group - Ridha Rizki Novanda; Ine Yunita Sari (Journal La Lifesci, 2021)
This research aims to identify the process of adopting innovation of calina papaya into Papaya Sauce for women farmer groups to increase the income of women farmer groups. The research was conducted in the village of Rindu Hati with a purposive method. The location selection was due to the existence of a farmer business group that cultivates and manages calina papaya. In this study, the determination of respondents was carried out by census with 32 female subjects who were cultivating and cultivating papaya plants. Data analysis used descriptive methods to assess the characteristics of the data. The results of the research are: First, the knowledge stage is in the medium category for the knowledge function and the high category for the knowing process. Second, persuasion forms a good attitude towards the adoption of innovation in the high category. Third, the getting to know stage is still in the Medium category. Fourth, the Implication stage using innovation is still relatively moderate. Fifth, confirmation of the adoption of papaya sauce innovation is still in the Medium category.